Impact of peanut seeding rate on water-use efficiency and yield - Zhang, Gengsheng; Leclerc, Monique Y.; Poudel, Kriti; Tubbs, Ronald Scott; Monfort, Walter Scott (Frontiers in Agronomy, 2025)
Seeds account for one of the highest costs in peanut production. Moreover, the climate in most of the Southeastern US is predicted to become drier and warmer throughout the growing season. Thus, this paper examines how seeding rates alter ecosystem water-use efficiency (WUE) and yield. Experiments with 31.2, 23.0, and 14.8 seed/m were conducted in irrigated fields in Plains, Georgia, US in 2020, 2021 and 2022. WUE was determined continuously at the field scale throughout the growing seasons using the eddy-covariance method. Results suggest that the impact of seeding rate on WUE is highly dependent on weather conditions. With ‘normal’ weather conditions in 2020, both the WUE expressed as the ratio of the net ecosystem exchange (NEE) of CO2 to evapotranspiration (ET) (noted as WUENEE) and the WUE as the ratio of gross primary productivity (GPP) to ET (WUEGPP) of 14.8 seed/m generally tended to be larger than those of 31.2 seed/m by 6-17% and 6-13% in all accumulated growing-degree day (aGDD) ranges respectively. In particularly wet 2021, both WUENEE and WUEGPP with 31.2 seed/m were larger than those with 23.0 and 14.8 seed/m. This may be because ET in the high seeding rate was hindered more than those in the lower seeding rates in such wet conditions. In contrast, the hot dry weather conditions early in 2022 season (aGDD 500-1000, the period of beginning bloom – full pod) led to high respiration rates with 14.8 seed/m and thus to much lower NEE values. As a result, WUENEE of the low seeding rate was much lower than those of 23.0 and 31.2 seed/m by 65% and 70% during the period respectively, but the WUEGPP of the low seeding rate was equivalent to those of the higher seeding rates. The mid seeding rate had the greatest yield among seeding rate treatments in the wet season and had yield equivalent to other seeding rates in other two years, making it the best option in this three-yr study. The mid seeding rate is recommended to obtain both high yield and high WUE in a hot dry year and high yield in a rainy year.